PENGEMBANGAN MEDIA SCRAFBOOK TERHADAP HASIL BELAJAR SISWA KELAS 1 SEKOLAH DASAR - Alvionita Sari, Vivi; Satrio Wibowo; Galuh Kartika Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The background of this researcher was to develop a scrafbook learning media to improve the learning outcomes of grade 1 students at SDN 3 Pucanga Sidoarjo on theme 1